2018
DOI: 10.1007/s12035-018-1300-9
|View full text |Cite
|
Sign up to set email alerts
|

Telmisartan Protects a Microglia Cell Line from LPS Injury Beyond AT1 Receptor Blockade or PPARγ Activation

Abstract: The Angiotensin II Receptor Blocker (ARB) Telmisartan reduces inflammation through Angiotensin II AT1 receptor blockade and peroxisome proliferator-activated receptor gamma (PPARγ) activation. However, in a mouse microglia-like BV2 cell line, imitating primary microglia responses with high fidelity and devoid of AT1 receptor gene expression or PPARγ activation, Telmisartan reduced gene expression of pro-injury factors, enhanced that of anti-inflammatory genes, and prevented LPS-induced increase in inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 163 publications
1
24
0
Order By: Relevance
“…The purified microglial cells were cultured at 37 °C in DMED-F12 medium (Gibco, CA, USA) containing 10% fetal bovine serum (Gibco, CA, USA). Seven days later, microglia were pre-treated with 40 μM ASA VI (Alfabiotech, Chengdu, China) or 10 μM GW9662 (Sigma-Aldrich, MO, USA) [ 24 ]. After 30 min, microglia were treated for 24 h with either 50 ng/mL lipopolysaccharide (LPS; Sigma-Aldrich, MO, USA) or phosphate-buffered saline (PBS; BOSTER, Wuhan, China) (control).…”
Section: Methodsmentioning
confidence: 99%
“…The purified microglial cells were cultured at 37 °C in DMED-F12 medium (Gibco, CA, USA) containing 10% fetal bovine serum (Gibco, CA, USA). Seven days later, microglia were pre-treated with 40 μM ASA VI (Alfabiotech, Chengdu, China) or 10 μM GW9662 (Sigma-Aldrich, MO, USA) [ 24 ]. After 30 min, microglia were treated for 24 h with either 50 ng/mL lipopolysaccharide (LPS; Sigma-Aldrich, MO, USA) or phosphate-buffered saline (PBS; BOSTER, Wuhan, China) (control).…”
Section: Methodsmentioning
confidence: 99%
“…Telmisartan is an angiotensin-II type 1 receptor blocker and peroxisome proliferator-activated gamma (PPARγ) agonist used to treat hypertension ( Benson et al ., 2004 ). PPAR activation suppresses inflammatory responses in neurons, endothelial cells, astrocytes, and microglial cells and promotes amyloid β clearance ( Camacho et al ., 2004 ; Elkahloun et al ., 2018 ). Telmisartan had protective effects on memory impairment, glial inflammation, and amyloid burden in a transgenic mouse model of AD ( Tsukuda et al ., 2009 ; Torika et al ., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…To test the hypothesis, we incubated an immortalized mouse microglialike BV2 cell line in an LPS-containing cell culture medium to mimic a neuroinflammatory environment (Lund et al, 2006). We found that the BV2 microglial cells mimicked primary microglia responses with high fidelity (Elkahloun et al, 2019) and were more tolerable for manipulating TREM2 overexpression. Because angiotensin II induces microglial activation through AT1R interacts with TLR4, and BV2 cells are devoid of AT1 receptor gene expression (Xu et al, 2015), BV2 cells are especially suitable for the present study to elucidate the mechanism focusing on TREM2-mediated microglial anti-inflammatory responses via LPS-ignited TLR4 pathway (Srinivasan et al, 2016;Zheng et al, 2016).…”
Section: Discussionmentioning
confidence: 99%